Rendahnya tingkat perilaku digital ASN kementerian kominfo: Survei literasi digital pada instansi pemerintah - Rumata, Vience Mutiara; Nugraha, Dimas Aditya (Faculty of Communications Science, Dr. Soetomo University, 2020)
â€œSDM Unggul Indonesia Majuâ€ became the theme of the 74th anniversary of the Republic of Indonesia in 2019. It is clear that the focus of the government under the leadership of President Joko Widodo is to develop human resources (HR) who can compete globally in the era of the industrial revolution 4.0, including the state civil apparatus (ASN). The applicable regulations require ASN to have technical competence because digital expertise is one of the skills that is very much needed now. However, there are no standard measurements related to digital expertise. To fill this gap, this research tried to develop a digital literacy framework for ASN which consists of three dimensions: the dimension of knowledge, the dimension of digital expertise, and the dimension of behaviour. We conducted an online survey at the Ministry of Communication and Information Technology with the result that 44.9 per cent of the 752 respondents had a good level of digital literacy. However, there were still 13.7 per cent of respondents who have a low level of digital literacy.